Sustainable Indigenous Knowledge Systems in Agriculture in Zimbabwe's Rural Areas of Matabelel and North and South Provinces : Zimbabwe Case Study - Sibanda, Harold (World Bank, Washington, DC, 2012)
This study researched Indigenous Knowledge Systems (IKS) in agriculture in Zimbabwe's rural areas, focusing on crop farming in the Tonga of Binga District in Matebeleland's North Province, and livestock in the Kalanga tribe of the Plumtree District in Matebeleland's South Province. The study aimed to uncover some of the knowledge that indigenous people used to survive under the harsh climatic and physical conditions of the region. Specific goals in both the Binga and Plumtree Districts were: 1) to uncover the socio-political, religious, economic, and environmental implications of IKS in farming; 2) to identify and analyze the methods of natural resources management; and 3) to assess the value and limitations of IKS in agriculture.